Novel missense mutation of the FAM83H gene causes retention of amelogenin and a mild clinical phenotype of hypocalcified enamel - Urzúa, Blanca; Martínez, Carolina; Ortega-Pinto, Ana; Adorno, Daniela; Morales-Bozo, Irene; Riadi, Gonzalo; Jara, Lilian; Plaza, Anita; Lefimil, Claudia; Lozano, Carla; Reyes, Monserrat (Archives of oral biology, 2015)
•In this paper a missense mutation in exon 5 of FAM83H gene was identified for the first time.•The missense variant, p.Gly557Cys, is associated with amelogenesis imperfecta hypocalcified.•The amelogenesis imperfecta phenotype is less severe than that observed in other similar cases reported.•The affected enamel is formed by prisms altered at ultrastructural level.•The affected enamel retains proteins amelogenin type. Amelogenesis imperfecta (AI) is a group of clinically and genetically heterogeneous inherited conditions, causing alterations in the structure of enamel and chemical composition of enamel matrix during development. The objective of this study was to compare the clinical, radiographic, histological and immunohistochemical phenotypes of subjects affected with hypocalcified AI from three Chilean families and identify causal mutations in the FAM83H gene. The diagnosis was made using clinical, radiographic, histological and genealogical data from the patients, who were evaluated according to the classification criteria by Witkop. PCR and Sanger sequencing of the complete coding sequence and surrounding intron regions of the FAM83H gene were conducted. The structural study of the affected teeth was performed with light microscopy, scanning electron microscopy and immunohistochemistry. The probands of the three families were diagnosed with hypocalcified AI, but in only one of them the missense variant p.Gly557Cys was identified. This variant was not present in the SNP database or in 100 healthy controls and segregated with the disease in the affected family. Using light microscopy, a normal prismatic structure was observed in all three cases. However, the ultrastructure was found to be affected in two of the cases, showing persistence of organic matter including amelogenins. These results suggest that FAM83H missense mutation reported in one of the families analyzed in this study might cause a phenotype of hypocalcified enamel more attenuated with retention of amelogenin.